FINAL DESTINATION DIAGNOSIS OF SOLID WASTE GENERATED IN RURAL SETTLEMENTS IN THE SERTÃO OF PARAÍBA, BRASIL - da Silva, Elisângela Maria; Arruda, Valmir Cristiano Marques; Miranda, Roberto de Sousa; Tavares, Rosângela Gomes; de Queiroz, Alessandro Pelópidas Ferreira (Revista Geama, 2017)
The increasing use of natural resources, the advancement of technology, changes in the needs established by the modern population, constituted by cultural aspects contribute significantly to the increase of solid waste generation in the urban and rural environment, thus necessitating more and more of adequate disposal end. Therefore, the objective of this work was to diagnose the final destination / treatment of the solid waste generated in two rural settlements, located in the municipality of Pombal-PB. Field visits were made in the settlements, in order to know the forms of solid waste disposal. It was possible to verify that more than 80% of the residents of the settlements, burn waste as an alternative for the disposal / treatment of solid waste. With this result, it was observed the need for an environmental awareness regarding the sustainable disposition of these residues in rural settlements.